Legal Intervention in Planning Regulations: Cooper v Wandsworth in a West African Context - Mensah, Kwadwo B. (Afrika Focus, 1996)
One of the most important problems facing many West African cities in recent times is rapid and seemingly uncontrollable urbanization '. The enormous pressure which these developments have had on public systems in general - sanitation, sewage, housing, health care and transport, has forced many cities to think of innovative ways of handling these crisis. Planning departments with substantial expertise in urban problems, are being set up or are being re-organized to meet these new challenges. The powers that planning departments have, and their impact on the lives of ordinary citizens cannot be over-estimated. To prevent abuse of power and to make them responsive to the needs of citizens, several methods are used to control them. Judicial review of administrative actions is the legal method used to control many public bodies in English speaking West African countries. In this article, I shall argue that in spite of its strengths, there is a general tendency to use judicial review to protect common law values like individual proprietary rights against the claims of state institutions. In West Africa, because of the weakness of public institutions, the intervention of the law, while protecting important private rights may hamper administrative effectiveness. Anticipating the use of the leading English case, Cooper v Wandsworth2 in reviewing planning decisions in West Africa, I shall conclude that such a position may not only diminish administrative effectiveness, but it may also diminish property rights. KEY WORDS: Planning, Administrative Effectiveness, Common Law in West Africa, Cooper v Wandsworth, Statutory Interpretation.